2020
DOI: 10.1111/jam.14737
|View full text |Cite
|
Sign up to set email alerts
|

The use of eugenol in combination with cefotaxime and ciprofloxacin to combat ESBL‐producing quinolone‐resistant pathogenicEnterobacteriaceae

Abstract: Aim Emergence of extended‐spectrum beta‐lactamase (ESBL) producing with quinolone‐resistant (QR) pathogenic Enterobacteriaceae augmented the need to establish therapeutic options against them. Present study aimed towards determination of synergistic combination of eugenol (EG) with cefotaxime (CTX) and ciprofloxacin (CIP) to combat against this resistance and potentiation of antibacterial drugs by EG against these bacteria. Methods and Results Synergistic interaction between EG and CTX/CIP (FICI: 0·08–0·5) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Combining these natural compounds with antibiotics constrains bacterial adaptation and restores antibiotic sensitivity by allowing the penetration of the latter [ 59 ]. Another reason for the synergetic effect is accounted to the ability of EG and CaRV to disrupt the bacterial cytoplasmic membrane, permeabilize the cell wall, enhance the expression of porins, and downregulate the efflux pumps, thus facilitating the uptake of the antibiotics [ 60 , 61 ]. Despite being terpenic components of essential oils, the effect of CaRV, CiNN, and EG vary due to the difference in their chemical structure, where the phenolic nature of CaRV and EG tend to exhibit a greater bactericidal effect when compared to aldehydes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining these natural compounds with antibiotics constrains bacterial adaptation and restores antibiotic sensitivity by allowing the penetration of the latter [ 59 ]. Another reason for the synergetic effect is accounted to the ability of EG and CaRV to disrupt the bacterial cytoplasmic membrane, permeabilize the cell wall, enhance the expression of porins, and downregulate the efflux pumps, thus facilitating the uptake of the antibiotics [ 60 , 61 ]. Despite being terpenic components of essential oils, the effect of CaRV, CiNN, and EG vary due to the difference in their chemical structure, where the phenolic nature of CaRV and EG tend to exhibit a greater bactericidal effect when compared to aldehydes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the earlier studies reported inhibitory potential of herbal compounds against antibiotic-resistant ATCC strains, and there are not enough studies with antibiotic resistance clinical strains and their gene expression. Similarly, the antibacterial activity of clove compounds is well known: 1) eugenol on ESBL-QR E. coli (quinolone resistant) has demonstrated a synergistic interaction with cefotaxime, and ciprofloxacin (MIC = 0.91-7.34 µg/mL), and shrinkage of cell surfaces with reduced cytoplasm among in others ESBL-QR strains (Dhara and Tripathi 2020). And 2) caryophyllene as β-caryophyllene was able to alter membrane permeability and integrity of B. cereus, leading to membrane damage and intracellular content leakage, which eventually caused cell death (MIC = 2.5% -v/v-) (Moo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For kinetic curve the times measured were 0, 2, 4, 6, 8, 12 h with a decrease of bacteria except for MBC at 6 h until 24 h an increasing of bacteria survival in comparison with control outpatients in Tabriz, Iran could be carriers of ESBL-E. coli with resistant genes, 2% of blaSHV and 4% of blaTEM (Dizage 2019). However, the combination between natural compounds and antibiotics (i.e., eugenol-cefotaxime) represents an important management to suppress the synthesis at transcript level in antibiotic-resistant genes (i.e., acrB) (Dhara and Tripathi 2020). Therefore, EOSA could be a potential such as adjuvant to combat certain infections caused by multidrug-resistant bacteria (i.e., ESBL-E. coli).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, eugenol was reported as having an inhibitory effect on NorA efflux pumps when combined with norfloxacin in S.aureus . Eugenol was also demonstrated to inhibit the arB gene with cefotaxim and ciprofloxacin in ESBL Enterobacteriaceae [ 65 , 66 ].…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%